Linfonodo-sentinela no câncer de cólon: comparação entre as técnicas in vivo e ex vivo - Antonio Hilario Alves Freitas (2012)
Each year, approximately 1,200,000 cases of colorectal cancer are diagnosed worldwide. Patients with early-stage disease, without lymph node metastatic, evolve with tumor recurrence or relapse in up to a quarter of cases, likely due tounderstaging. The objective is to research sentinel lymph nodes in patients with colon adenocarcinomas, comparing in vivo and ex vivo techniques used in their identification, and to detail anatomical-pathological examination, with multisectionand immunohistochemistry, of these lymph nodes. Thirty-three patientsundergoing curative cancer surgery were studied. The marker used to identify sentinel lymph nodes was patent blue dye. In 18 of these patients, the dye was injected in vivo into the peritumoral subserosa, while with 15 patients, it was injected ex vivo into the peritumoral submucosa. The visual identification of sentinel lymph nodes with the dye was possible in 72.2% of the in vivo cases, and in 33.3% of the ex vivo cases. In routine histopathological analysis, the sensitivity for detection of metastases in sentinel lymph nodes was 66.7% in vivo, and 100% ex vivo; alse- negatives were 33.3% for the in vivo group, and zero ex vivo. Amongpatients without metastases by routine histopathological examination with hematoxylin-eosin, examination with multisection and immunohistochemistry of sentinel lymph nodes diagnosed metastases in one (9%) subject from the in vivo group and in one subject (14.3%) from the ex vivo group, leading to a consideration of restaging. We conclude that in the identification of sentinel lymph nodes, in vivo research yielded better results than the ex vivo approach. Thediagnosis of metastases by routine histopathology was proportionally the same in sentinel and non-sentinel lymph nodes. The antomical- pathological techniques of multisection and immunohistochemistry improved the staging of tumors, compared to routine histopathological examination.